Nonlinear localized longitudinal waves in a plate under magnetic field - Erofeyev, Vladimir Ivanovich; Zemlyanukhin, Alexandr Isaevich; Catson, Vladimir Markovich; Malkhanov, Alexey Olegovich (Computational Continuum Mechanics, 2010)
We consider an elastic plate made of a conducting material under external magnetic field conditions. It is shown that the propagation of intense waves in this system can be described by the nonlinear evolutionary equation, which combines the well-known Khokhlov-Zabolotskaya-Kuznetsov and Kodomtsev-Petviashvili model equations. The peculiarities of propagation of 2D nonlinear magnetoelastic waves have been analyzed both analytically and numerically.
Keywords: magnetoelasticity; elastic waves; magnetic field; plate